Implementation Of Asean Human Rights Declaration In The Protection Of Women And Children's Rights - Meilyska Purba (International Journal on Social Science, Economics and Art, 2020)
Various human rights legal instruments, both international, regional and domestic, has become an agreement to be executed by the state to guarantee the protection of freedom-freedom for every individual. In accordance with the contents of the ASEAN Human Rights Declaration on the 4th principle that " The rights of women, children, the elderly, persons with disabilities, migrant workers, and vulnerable and marginalized groups are part of human rights and fundamental freedoms are inherent, fused, and inseparable". However, an implementation up to now is still lacking the benefit of this declaration. However, do not lose hope that the important thing is how to ensure the implementation of this declaration in order to be implemented as well as possible. To all those of stakeholders help to succeed in the implementation of this declaration which ensure the implementation and implement programs that have been planned. So important is the issue of human rights, it becomes interesting to study through this paper, how the promotion and protection of human rights committed in the context of international relations, particularly through the actors that have influence and can also act internationally on many levels.